The relationship between occupational stress burnout and job performance among teachers in basic education schools in Muscat - Hamed Al-Wahshi, Salwa Khalifa (OCERINT International, 2020)
The aim of the research is to discuss the relationship between psychological stress, burnout and the job performance of teachers. The researcher prepared a measure of psychological burnout, after referring to the literature and some measures of psychological burnout, including the Maslash scale of psychological combustion, which was adopted by many studies. A psychological stress scale was also developed, where the researcher reviewed the teachers ’psychological stress scale (1989). The researcher used the descriptive "relational" approach. The research sample consisted of (200) male and female teachers distributed in (10) schools for males and females. The study concluded the following results: There is a correlation between occupational stress and the total dimensions of burnout at the level of (0.01). The study also found that there is no statistically significant relationship between occupational stress and job performance. Also, there is no statistically significant relationship between burnout in its four dimensions and the job performance of the teacher. It also became clear through the study that there is no statistically significant relationship between the physical dimensions of combustion and the job performance. The study also found that there were no differences between male and female teachers with regard to total burnout. Despite that, there is a difference between the two averages, which suggests that there are differences in males that they are less burning than females.